BUSINESS ETHICS VALUES IN MUI FATWA NO. 83 OF 2023 - Fatimah, Syarifah; Asnawi, Nur; Khasanah, Umrotul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
MUI Fatwa No. 83 of 2023 contains an appeal to avoid buying products affiliated with Israel as a reaction to the military attacks carried out by Israel against the Palestinian people. This movement is not only a movement based on religion alone but also an effort to stop the violence that continues to occur. This research aims to uncover the basis for issuing the fatwa and find the business ethical values ​​in the fatwa. Using qualitative research methods and a normative and historical approach, this research takes data sources through previous research journals, books related to the theme, websites and primary data in the form of the MUI Fatwa discussed. There are three foundations underlying the MUI fatwa, namely the normative basis contained in the Koran, hadith and the opinions of ulama, the historical basis from various points of view and the ethical basis using an Islamic business ethics approach. The normative foundation of Islamic business ethics consists of four ethical axioms, namely the foundation of monotheism, the foundation of balance and justice, the foundation of free will, and the foundation of responsibility. Although the boycott of Israeli-affiliated products in Indonesia presents a challenging ethical dilemma, it is also indirectly an effort to offer a constructive solution.